The Effect of Accountability, Competence, and Independence on Audit Quality - Assegaff, Syarifah Dahlia (Advances in Managerial Auditing Research, 2024)
Purpose: This study aims to analyze and examine the impact of accountability, competence, and independence on audit quality in public accounting firms in Makassar City. Research Design and Methodology: The research utilizes a descriptive and multiple regression analysis to assess the data collected from a sample of 34 respondents. The study investigates the simultaneous and partial effects of accountability, competence, and independence on audit quality. Findings and Discussion: The results indicate that accountability, competence, and independence positively and significantly influence audit quality in public accounting firms in Makassar City. The findings suggest that these factors are crucial for ensuring high audit quality, confirming that auditors' professional behavior, skills, and ability to remain objective contribute significantly to reliable and credible audit outcomes. Implications: The study provides valuable insights for public accounting firms, emphasizing the need to enhance auditor training in accountability, competence, and independence. By investing in continuous education and professional development programs, firms can improve auditors' performance and, consequently, audit quality. This research also lays the groundwork for further studies to explore these factors in different cultural and regulatory contexts, enhancing the generalizability and applicability of the findings.